ASSESSMENT OF PROGNOSIS IN PATIENTS WITH INVASIVE BREAST CANCER AND METASTATIC SENTINEL LYMPH NODE TREATED WITH OR WITHOUT AXILLARY LYMPHADENECTOMY - Sanvido, Vanessa Monteiro; Elias, Simone; Nazário, Afonso Celso Pinto (Mastology, 2020)
Introduction: The American College of Surgeons Oncology Group (ACOSOG) Z0011 trial was a landmark in axillary surgical treatment. Its results brought significant contributions to the reduction of the extension of breast cancer surgery. However, this approach was questioned at first. Objectives: To assess the global survival and the locoregional recurrence in patients with metastatic sentinel lymph node biopsy treated with or without axillary lymphadenectomy (AL). Method: A historical cohort study was carried out with patients with primary invasive breast carcinoma and clinically negative axilla who underwent breast-conserving surgery and SLNB between February 2008 and December 2018. Results: We included 415 patients who were submitted to conserving surgery. In 23.3% (97 patients), SLNB was positive, 56 patients were submitted only to SLNB, and 41 patients were treated with AL. The groups were homogeneous regarding the variables: age group (p=0.279), anatomopathological diagnosis (p=0.210), histological grade (p=0.983), hormone receptor expression (p=0.708), HER 2 expression (p=0.695) and pT (p=0.334). Global survival, in the mean period of 5 years, was 80.1% in the SLNB group, and 87.5% in the AL group (p=0.376). The locoregional recurrence was a rare event; in the mean period of 5 years, there was 1.8% in the SLNB group, and 7.7% in the AL group (p=0.196). Only 4 locoregional recurrences were described, and all took place in up to 18 months of follow-up. Conclusions: Global survival and locoregional recurrence in patients with metastatic axillary sentinel lymph node treated only with sentinel lymph node biopsy did not present diffe-rences in relation to patients who underwent axillary lymphadenectomy, which corroborates the data from ACOSOG Z0011. The omission of axillary lymphadenectomy and the implantation of such a practice in our service benefitted the patients treated with less aggressive surgery, and, potentially, with lower morbidity.